Adding genetic risk score to family history identifies twice as many high‐risk men for prostate cancer: Results from the prostate cancer prevention trial. Issue 12 (16th May 2016) - Chen, Haitao; Liu, Xu; Brendler, Charles B.; Ankerst, Donna P.; Leach, Robin J.; Goodman, Phyllis J.; Lucia, M. Scott; Tangen, Catherine M.; Wang, Li; Hsu, Fang‐Chi; Sun, Jielin; Kader, A. Karim; et al.
Abstract : BACKGROUND: While family history (FH) has been widely used to provide risk information, it captures only a small proportion of subjects with higher genetic susceptibility. Our objective is to assess whether a genetic risk score (GRS) calculated from prostate cancer (PCa) risk‐associated single nucleotide polymorphisms (SNPs) can supplement FH for more effective risk stratification for PCa screening decision‐making. METHODS: A GRS was calculated based on 29 PCa risk‐associated SNPs for 4, 528 men of European descent in the placebo arm of the Prostate Cancer Prevention Trial (PCPT). At study entry, participants were free of PCa diagnosis. Performance of FH and GRS were measured by observed detection rate of PCa and high‐grade PCa (Gleason score ≥7) during the 7‐year study. RESULTS: GRS was a significant predictor of PCa in men with or without a positive FH ( P  = 1.18 × 10 −4 and P  = 4.50 × 10 −16, respectively). Using FH alone, as expected, the 17% of men who were FH+ had a PCa detection rate that was significantly higher (29.02%) than FH− men (23.43%, P  = 0.001). When both FH+ or GRS >1.4 are considered, more than twice as many men (36%) can be classified as higher risk, as evidenced by a significantly higher PCa detection rate (30.98%) than in the remaining men (20.61%, P  = 5.30 × 10 −15 ). If targeting only FH+ men, four out of five PCa cases would go undetected, as would a similarly large fraction (∼80%) of high‐grade PCa cases. In comparison, if targeting FH+ or GRS >1.4 men, almost half of all PCa cases would be detected, including 45% of high‐grade PCa cases. CONCLUSIONS: A prostate cancer GRS can supplement family history to better identify higher risk men for targeted intervention. Prostate 76:1120–1129, 2016 . © 2016 Wiley Periodicals, Inc.